2009
DOI: 10.14411/eje.2009.058
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting levels of polymorphism in cross-amplified microsatellites in two endangered xerothermophilous, obligatorily myrmecophilous, butterflies of the genus Phengaris (Maculinea) (Lepidoptera: Lycaenidae)

Abstract: Abstract.We analysed the polymorphism of cross-amplified microsatellite loci in two endangered butterflies of the genus Phengaris, which inhabit warm grasslands. Specimens of P. arion and P. 'rebeli' collected in Poland showed contrasting levels of variability in the investigated loci. All six tested microsatellites were highly variable in P. arion, whereas in P. 'rebeli' one locus was monomorphic and the other four loci showed a rather low level of polymorphism. Genetic differentiation was small or moderate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 72 publications
3
30
1
Order By: Relevance
“…Small pieces of wings were torn off using tweezers and placed into containers with 95% ethanol. DNA was extracted using a Genomic Mini Kit (A&A Biotechnology) as described in Rutkowski et al (2009). DNA polymorphism was assessed using microsatellite loci.…”
Section: Genetic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Small pieces of wings were torn off using tweezers and placed into containers with 95% ethanol. DNA was extracted using a Genomic Mini Kit (A&A Biotechnology) as described in Rutkowski et al (2009). DNA polymorphism was assessed using microsatellite loci.…”
Section: Genetic Studymentioning
confidence: 99%
“…DNA polymorphism was assessed using microsatellite loci. We PCR-amplified five microsatellite loci, characterized by Zeisset et al (2005) as Macu5, Macu8, Macu11, Macu15 and Malc169, using primers as described by the authors and reagents and conditions as described by Rutkowski et al (2009). The length of the amplified fragments was estimated using a CEQ8000 Beckman Coulter automated sequencer (Beckman Coulter, Inc., Brea, CA, USA; agency in Poland: Comesa, Warsaw), and subsequently the chromatograms were analysed using Beckman Coulter Fragment Analysis Software in order to obtain into the individual genotypes.…”
Section: Genetic Studymentioning
confidence: 99%
“…Laboratory procedures DNA was extracted from approximate 0.5 cm long fragments of thorax or from the whole leg, as described in Rutkowski et al (2009). Using the PCR reaction we amplified six microsatellite loci, designated by Zeisset et al (2005) as Macu8, Macu9, Macu11, Macu15, Macu16 and Macu17 using primers described by the authors.…”
Section: Localities and Samplingmentioning
confidence: 99%
“…P. alcon and P. nausithous (Zeisset et al 2005), and used in the investigation of the molecular ecology of these species (Anton et al 2007;Nash et al 2008) may also be successfully applied in studies of P. arion. Preliminary data on the genetic structure of the butterfly in Poland also indicated moderate genetic differentiation among populations, but simultaneously suggested that some pairs of populations could be highly differentiated, despite spatial (geographical) closeness (Rutkowski et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation